Aza follow-ups to BI 207524, a thumb pocket 1 HCV NS5B polymerase inhibitor. Part 1: Mitigating the genotoxic liability of an aniline metabolite. Issue 5 (1st March 2015) - Beaulieu, Pierre L.; Bolger, Gordon; Duplessis, Martin; Gagnon, Alexandre; Garneau, Michel; Stammers, Timothy; Kukolj, George; Duan, Jianmin
Graphical abstract: Abstract: A series of heterocyclic aza-analogs of BI 207524 (2 ), a potent HCV NS5B polymerase thumb pocket 1 inhibitor, was investigated with the goal to reduce the liability associated with the release of a genotoxic aniline metabolite in vivo. Analog4, containing a 2-aminopyridine aniline isostere that is negative in the Ames test was identified, and was found to provide comparable GT1a/1b potency to2 . Although the cross-species PK profile, poor predicted human liver distribution of analog4 and allometry principles projected high doses to achieve a strong antiviral response in patients, this work has provided a path forward toward the design of novel thumb pocket 1 NS5B polymerase inhibitors with improved safety profiles.